2014
DOI: 10.1144/m39.5
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 5 Vulcanian explosions at Soufrière Hills Volcano, Montserrat between 2008 and 2010

Abstract: Vulcanian explosions generated at Soufrière Hills Volcano between 2008 and 2010 varied from simple events involving minimal pyroclastic density currents (PDCs) to complex events involving more than one explosion. Calculated volumes for the deposits of the PDCs formed by these explosions ranged up to 2.7×106 m3, with more than half the explosions having volumes greater than 1×106 m3. The deposits formed by the explosions varied in lithology, with some explosions generating pumice-rich PDCs (e.g. 29 July 2008 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…Accordingly, the total discharged plume volume of 0.8 Â 10 6 -20.2 Â 10 6 m 3 is estimated by integrating the volume flux on the 22 s-long gas-thrust phase, that would give a total discharged mass of 5.4 Â 10 6 -272 Â 10 6 kg. This is in agreement with previous estimates using different methods from other Vulcanian eruptions at SHV (Druitt et al 2002;Formenti et al 2003;Komorowski et al 2010;Cole et al 2014).…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Accordingly, the total discharged plume volume of 0.8 Â 10 6 -20.2 Â 10 6 m 3 is estimated by integrating the volume flux on the 22 s-long gas-thrust phase, that would give a total discharged mass of 5.4 Â 10 6 -272 Â 10 6 kg. This is in agreement with previous estimates using different methods from other Vulcanian eruptions at SHV (Druitt et al 2002;Formenti et al 2003;Komorowski et al 2010;Cole et al 2014).…”
supporting
confidence: 93%
“…This VLP seismic signal with a frequency of 0.04 Hz seems to be a typical feature of large Vulcanian explosions at SHV, at least in the 2008-2010 period (Cole et al 2014), but not previously reported. Nevertheless, ultra-low-period (ULP .100 s) seismic signals have been recorded by broadband seismometers at SHV (Green & Neuberg 2005) and explained as being related to the pressurization of the upper conduit, presumably by a trapped gas phase.…”
supporting
confidence: 50%
See 2 more Smart Citations
“…Druitt et al 2002;Cole et al 2014;Wadge et al 2014). The explosions have occurred as isolated events, as part of month-long sequences, or associated with dome collapse events (Edmonds et al 2006;Loughlin et al 2010;Cole et al 2014).…”
mentioning
confidence: 99%